Kearifan Lokal Dalam Teks Berita Lelayu di Lingkungan Etnik Jawa - Sudiyana, Benedictus; Marmoah, Sri; Nurhasanah, Farida; Wicaksana, Muhlis Fajar (Universitas Batanghari Jambi, 2023)
The news text that grew up among Javanese ethnicity highlighted a lot of local wisdom, one of which was religious value. This study aims to describe the practice of local wisdom in Javanese lelayu news texts in the Yogya-Surakarta community. The research method is carried out with qualitative descriptive of text objects. Data in the form of words, language expressions, phrases, clauses, and sentences, which contain positive value messages as expressions and representations of mikul dhuwur mendhem jero in withered news texts. Data collection is carried out by recording text based on criteria of data characteristics. Data analysis was carried out by utilizing the fields of linguistic semantics, language variety, pragmatics, and representation of social actors, with identification, classification, and interpretation procedures as qualitative research steps. The results showed that the disclosure of the value of